The use of online forums by people living with HIV for help in understanding personal health information. (December 2017) - Bussone, Adrian; Stumpf, Simone; Wilson, Stephanie
Highlights: HIV+ people use online forums to seek input on their health information. Questions were most commonly about causation and normalcy. A variety of personal health information is shared to provide context for questions. Community members addressed questions with informational support and personal experiences. Abstract: Purpose: Effective self-management of the human immunodeficiency virus/acquired immune deficiency virus (HIV/AIDS) requires constant vigilance over personal health information. Little is known about the contribution of online communities to this endeavour. This paper reports a study to investigate how people living with HIV/AIDS use an online community to try to understand their personal health information by analysing how health information is shared and asked about, and how the community responds to questions. Methods: A webscraper was used to gather all messages in the 200 most recently active threads in an online forum for people living with HIV/AIDS, resulting in a total of 2455 messages. These were filtered for all instances of individuals sharing their personal health information and asking the community for help in understanding it. Thematic analysis was used to determine the types of questions asked, the personal health information shared and the information that was asked about. Messages from the community aiming to address the questions were analysed using a framework of social support. Results: Approximately 10% of the 2455 messages were found to be involved in this activity: 60 messages contained questions, and 192 messages responded to address the questions. The most frequent type of question was about causation. While users shared a wide variety of information about their health, they most commonly asked about reactions, lab results, and other conditions. Nearly all the messages from the community that aimed to answer the questions provided informational support, which is a type of social support, and the community shared their own personal experiences in these responses. Conclusions: This study demonstrates that online forums are used by people living with HIV to ask specific questions as a means of understanding their personal health information. The analysis provides a better understanding of the questions that people living with HIV have about their health information, and the types of support they receive from the community. The results provide a basis for further research into community support and self-management and will enable improved tools to support self-management.